Knowledge and satisfaction of the antivectorial campaign workers against Aedes aegypti - Isolina Sánchez Jacas; Elizabeth Delás Jaen; Henry Darío Suárez Vélez (Centro Provincial de Información de Ciencias Médicas, 2016)
A qualitative evaluative investigation was carried out in the Vectors Control Department of "Carlos Juan Finlay" Teaching Polyclinic in Santiago de Cuba, during January-May, 2013, with the purpose of evaluating the work quality of A, B operator and brigade chiefs, starting from their knowledge for an efficient performance in the control of Aedes aegypti, and on the base of criteria, indicators and standards elaborated for the purpose.  It was concluded that workers didn't possess the necessary knowledge and were not satisfied with the conditions and working performance, because the established criteria were inadequate in all of them; as for the satisfaction of the residents, just 8 criteria were adequate.  This way, it could be concluded that the operators and brigade chiefs didn't master the daily activities of the antivectorial campaign.